Novel malaria vaccines - Matthew B. Laurens (Taylor & Francis Group, 2021)
Malaria vaccines hold significant promise for life-saving benefit, especially to children who bear the major burden of malaria mortality. The RTS,S/AS01 malaria vaccine provides moderate efficacy and is being tested in implementation studies. In parallel, multiple strategies are being advanced to test next-generation malaria vaccines, including novel approaches that build on principles learned from RTS,S development, vaccination with radiation-attenuated sporozoites, and development of monoclonal antibodies targeting immunogenic peptides. Novel vaccine delivery approaches are also being advanced, including self-amplifying RNA vaccine delivery, self-assembling protein nanoparticle methods, circumsporozoite protein-based approaches, and whole organism vaccination. Techniques employed for COVID-19 vaccine development should also be considered for malaria vaccination, including sustained release polymer nanoparticle hydrogel vaccination and charge-altering releasable transporters. As vaccine science advances and new approaches optimize knowledge gained, highly effective malaria vaccines that provide sustained protection are within reach.